Role of ferroptosis-related IREB2 in the shared genetic etiology between smoking and facial aging: Insights from large-scale genome-wide cross-trait analysis - Xueyao Cai; Weidong Li; Wenjun Shi; Yuchen Cai; Jianda Zhou (Computational and Structural Biotechnology Journal)
While the association between smoking and accelerated facial aging is well documented, the specific pathways underlying this association remain poorly understood. To investigate the shared genetic architecture between smoking and facial aging, we performed genetic analyses based on genome-wide association studies (GWAS) data. These analyses included linkage disequilibrium score regression (LDSC), pleiotropic analysis under composite null hypothesis (PLACO), functional mapping and annotation (FUMA), and multi-marker analysis of genomic annotation (MAGMA). To further explore the shared target genes, we utilized expression quantitative trait loci (eQTLs) and mediation Mendelian randomization (MR) analysis, with subsequent validation conducted through in vitro experiments using NIH/3T3 cells. Additionally, we carried out pan-cancer correlation analyses to assess the broader implications of the identified genes in cancer biology. Through pleiotropy and colocalization analyses, IREB2, along with CHRNA5 and AARS1, were identified as having strong evidence linking smoking and facial aging. Functional enrichment, tissue-specific analyses, and gene co-expression network were conducted to further elucidate the functions of these genes. Following eQTLs and mediation analyses, IREB2 was identified as a potential mediator connecting smoking to facial aging. Cellular experiments demonstrated that exposure to cigarette smoke particles induces cellular senescence and downregulates IREB2 expression. The pan-cancer analysis highlighted IREB2's role in shaping the tumor microenvironment and influencing immune processes. This study identifies IREB2 as a critical factor in the molecular mechanisms by which smoking accelerates facial aging, while also contributing to tumor development and immune evasion. Further functional exploration of IREB2 could uncover new therapeutic avenues to address these interconnected conditions.